STUDI TENTANG PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DAN MADRASAH - Efendi, Asip; Pahrudin, Agus; Jatmiko, Agus; Koderi (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
Developing the Islamic Religious Education curriculum in Indonesia is very important and urgent due to changing social, cultural, and technological dynamics. This study aims to analyze the development of the Islamic Religious Education curriculum in schools and madrasahs in Indonesia, which is increasingly important given social, cultural, and technological changes that affect the needs of learners. This research is expected to provide practical recommendations for improving the quality of religious education through a relevant and effective curriculum. The research method used is a descriptive qualitative approach, with data collected through observation, in-depth interviews, and document analysis, such as syllabi and lesson plans. Data analysis was conducted using an interactive method to find the main themes in implementing the Islamic Religious Education curriculum. The results show that most teachers still need the training to understand the